KEMANDIRIAN EKONOMI LEMBAGA PENDIDIKAN ISLAM MELALUI SOCIAL ENTREPRENEURSHIP - Fadhilla Washilla; Yusuf Effendi; Agung Safitri; Subandi Subandi; Amiruddin Amiruddin (Jurnal Manajemen Pendidikan, 2026)
This study aims to formulate a conceptual model of institutional economic independence through social entrepreneurship in Islamic educational institutions. The issue is important because many educational institutions depend on tuition, donations, and unstable external support, while social expectations toward access, quality, and community empowerment continue to increase. Methods: This article uses an integrative literature review by synthesizing studies on social entrepreneurship, hybrid organization, nonprofit finance, pesantren business units, cooperative governance, and sustainable institutional management. The analysis was conducted through thematic coding, conceptual comparison, and model construction. Results: The study identifies five interrelated elements of economic independence: asset mapping, social value proposition, diversified income portfolio, hybrid governance, and impact-based reinvestment. Social entrepreneurship enables institutions to generate revenue without abandoning their educational and social missions, provided that accountability, transparency, mission protection, and stakeholder participation are institutionalized. Novelty: The article offers an institutional economic independence model that integrates global social entrepreneurship theory with the Indonesian Islamic education context. The proposed model positions business activities not as commercial deviation, but as a mission-driven strategy to strengthen educational sustainability, social impact, and community welfare.